(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the role and didactic advantages of implementing a creative approach in teaching Information Technologies and the Mathematical Modeling of Processes. In the context of a rapidly developing digital environment, it is essential to cultivate students’ analytical thinking, mathematical–applied competence, and the ability to integrate modeling processes with technological solutions. Therefore, introducing creative tasks, problem-based learning, project-based methods, digital simulations, interactive models, visualization platforms, and real-time modeling tools significantly enhances the effectiveness of the learning process. During the research, a creative approach–based methodological model was designed, and its structural components—motivational, cognitive, practical, and reflective stages—were examined in detail. The findings indicate that students engaged in creative learning environments develop a deeper understanding of modeling algorithms, strengthen independent use of technological tools, and demonstrate improved abilities to propose innovative solutions to problem situations. This methodology can be effectively applied in the training of future specialists in medicine, engineering, economics, and other interdisciplinary fields.